Analisis Troublehooting Starter Motor terus berputar saat putaran APU Engine mencapai 50% rpm - Slamet Firdaus, Fazrin Andhika; MAMIN, MAMIN (Universitas Majalengka, 2022)
Airplanes are a universal means of transportation, with planes, we don't have to worry about the time when we want to go anywhere because with airplane transportation we can go anywhere in an efficient and short time. In this day and age, aircraft technology is very advanced. The aircraft component itself consists of several components, namely the Auxiliary Power Unit (APU). The APU functions to supply pneumatic and electrical energy for aircraft, where the electrical functions for electricity on the aircraft while pneumatic functions for engine starting, hydraulic pressure, air conditioning and others. This research method is descriptive research consisting of drafting, data collection, data processing and report preparation. In this step there are more stages which will later serve to get a conclusion in the study. Basically the trouble that often occurs when the APU starting process is on the starter motor component, Troubleshoot that often occurs in the starter motor component, namely the starter motor will continue to rotate when it reaches 50% rpm rotation caused by a starter motor problem, starter relay problem and electronical speed switch problem. Therefore, we must immediately repair or replace these components according to the aircraft maintenance manual so that the aircraft remains airworthy.